Knowledge and skills of primary health care workers trained on integrated management of neonatal and childhood illness: Follow-up assessment 3 years after the training - J Venkatachalam; Dinesh Kumar; Madhu Gupta; Arun Kumar Aggarwal (Wolters Kluwer Medknow Publications, 2011)
Background: The primary health care workers of a district in northern India were trained in the year 2006 for Integrated Management of Neonatal and Childhood Illness (IMNCI) using two different training methods: conventional 8-day training and new interrupted 5-day training. Knowledge and skills may decline over a period of time. Rate of decline may be associated with the type of training. A study was thus conducted to see the retention of knowledge and skills in the two training groups, 3 years after the initial training. Materials and Methods: This study was done in the Panchkula district of Haryana state in northern India. In the year 2006, 50 primary health care workers were given new interrupted 5-day training and another 35 workers were given conventional 8-day training on IMNCI. Knowledge and skills of the same workers were evaluated in the year 2009, using the same methodology and tools as were used in the year 2006. Data analysis was done to see the extent of decline in knowledge and skills in these 3 years and whether decline was more in any particular training group. Results: Compared to post-training score in the year 2006, composite knowledge and skill scores for Auxilliary Nurse Midwives (ANMs) and Anganwari workers (AWWs) together declined significantly in the year 2009 from 74.6 to 58.0 in 8-day training group and from 73.2 to 57.0 in 5-day training group (P < 0.001). Follow-up composite scores in the two training groups were similar. Whereas the decline was more for knowledge scores in 8-day training group and for skill score in 5-day training group, the pattern of decline was inconsistent for different health conditions and among ANMs and AWWs. Conclusion: Long-term retention of knowledge and skills in 5-day group was equivalent to that in 8-day training group. Refresher trainings may boost up the decline in the knowledge and skills.